Long-term effectiveness of population-wide multifaceted interventions for hepatocellular carcinoma in Taiwan - Liao, Sih-Han; Chen, Chi-Ling; Hsu, Chen-Yang; Chien, Kuo-Liong; Kao, Jia-Horng; Chen, Pei-Jer; Chen, Tony Hsiu-Hsi; Chen, Chien-Hung (Journal of hepatology, 2021)
Taiwan has launched a series of population-wide interventions to prevent hepatocellular carcinoma (HCC) related to hepatitis B and C virus infection since 1984. We took this opportunity to investigate the impact of each intervention on the incidence and case-fatality rate of HCC, and assessed their relative contributions to the overall reduction in mortality during this period. Population-based registry data on HCC mortality and incidence from individuals aged 0 to 84 years between 1979 and 2016 were collected before (Period 1) and after universal hepatitis B vaccination from 1984 (Period 2), universal health care from 1995 (Period 3), and viral hepatitis therapy from 2003 (Period 4). A Bayesian Poisson regression model was used for mortality decomposition analysis to estimate the respective contributions of these interventions to the reduction in age-specific incidence and case-fatality rates. Mortality declined substantially in children, young- and middle-aged groups, but only slightly decreased in the elderly group. The declining trends in mortality were in part explained by incidence reduction and in part by a remarkable decline in case-fatality rate attributed to universal health care. Hepatitis B vaccination led to a 35.9% (26.8% to 44.4%) reduction in incidence for individuals aged 30 years or below, whereas antiviral therapy reduced the incidence of HCC by 14.9% (11.8% to 17.9%) and 15.4% (14.1% to 16.6%) for individuals aged 30–49 years and 50–69 years, respectively. Vaccination and antiviral therapy were effective in reducing HCC incidence and mortality for the young and middle-aged groups, while the case-fatality rate was improved by universal health care for all age groups. Since 1984, a series of population-wide interventions have been launched in Taiwan to prevent viral hepatitis-related hepatocellular carcinoma, including a universal hepatitis B vaccination program (from 1984), universal health care (from 1995), and a national viral hepatitis therapy program (from 2004). Vaccination and antiviral therapy were effective in reducing HCC incidence and mortality for the young and middle-aged groups, while the case-fatality rate was improved by universal health care for all age groups. [Display omitted] •We assessed the impact of serial population-wide prevention programs on HCC mortality (incidence and case-fatality rates).•Hepatitis B vaccination was associated with a 35.9% reduction in incidence in the young age group.•Antiviral therapy was associated with a ~15% decline in incidence in the middle-aged group.•Surveillance resulted in a remarkable decline in the case-fatality rate across the whole population.